2015
DOI: 10.1152/ajpheart.00867.2014
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic reactivity in young women with a family history of hypertension

Abstract: Young adults with a family history of hypertension (+FH) have increased risk of developing hypertension. Furthermore, the blood pressure (BP) response to sympathoexcitatory stimuli in young adults can predict the future development of hypertension. Therefore, we hypothesized young women with a +FH would have exaggerated cardiovascular and sympathetic reactivity compared with young women without a family history of hypertension (-FH). Beat-by-beat mean arterial pressure (MAP) and muscle sympathetic nerve activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 58 publications
2
39
0
Order By: Relevance
“…These differences across studies are likely due to a number of methodological details and higher degree of interindividual variability. In contrast to the reported variability of BMI and resting BP in subjects with and without FHH, there appears to be consistency across laboratories regarding (3,18,22,26,35,44). In one study (31), subjects with extreme and complicated FHH (i.e., concomitant grade III or IV retinopathy) demonstrated higher resting MSNA than subjects without FHH; however, the impact of the underlying retinopathy in that study remains unclear (31).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…These differences across studies are likely due to a number of methodological details and higher degree of interindividual variability. In contrast to the reported variability of BMI and resting BP in subjects with and without FHH, there appears to be consistency across laboratories regarding (3,18,22,26,35,44). In one study (31), subjects with extreme and complicated FHH (i.e., concomitant grade III or IV retinopathy) demonstrated higher resting MSNA than subjects without FHH; however, the impact of the underlying retinopathy in that study remains unclear (31).…”
Section: Discussionmentioning
confidence: 91%
“…Greaney et al (18) recently reported a greater MSNA reactivity to cold pressor test in adults with FHH than those without FHH. However, others have reported that MSNA reactivity to cold pressor test was not significantly influenced by FHH (3) or was actually heightened in subjects without FHH compared with those with FHH (26).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There are emerging data indicating aberrant neural cardiovascular control in young adults with a family history of hypertension (+FH; Greaney et al . ; Fonkoue et al . ).…”
Section: Introductionmentioning
confidence: 99%